DevSecOps in practice with VMware Tanzu : building, running, and managing secure multi-cloud apps at scale on Kubernetes with the Tanzu portfolio /: building, running, and managing secure multi-cloud apps at scale on Kubernetes with the Tanzu portfolio. (2023) - Pandit, Parth; Hardt, Robert
No abstract available